Effectiveness of Nurse Led Clinical Interventions, on Physiological Outcomes among Patients Undergoing Hemodialysis - Rajanna, Shobha Kadabahalli; Sams, Larissa Martha (Journal of Neonatal Surgery, 2025)
Introduction and Aim: Hemodialysis is the most widely used treatment for severe and irreversible renal failure. Even in the best of circumstances, adjusting to the effects of renal failure and the dialysis period can be challenging. The patient may experience a decrease in energy in addition to the "lost time." The purpose of this study is to evaluate the effectiveness of video-assisted instruction on specific nurse-led therapeutic interventions to enhance the physiological outcomes of hemodialysis patients. Materials and Methods: 120 hemodialysis patients were recruited and allocated to intervention (n = 60) and control groups (n =60 ) using an evaluative pre-test and post-test repeated measure study design with the control group. Patients in the intervention group received intervention in terms of watching a video clip (40 minutes) - the video consist of disease condition, hemodialysis, dietary habits, fluid restriction, sleep hygiene, meditation, and yoga techniques, for two weeks after pre-test, later practice session, and group discussion along with individualised teaching and counselling session, finally a regular weekly follow up at dialysis unit, while the control group received only routine care. Results: In the intervention group there was a gradual improvement, in selected physiological outcomes and most of them remain the same without much change including, blood pressure, sodium, potassium, calcium, phosphorus and Hemoglobin level. In the control group, they did not change the physiological outcomes, in most of the patients. Conclusion: Nurse-led clinical treatments are beneficial, safe, necessary, natural therapies that can be administered under supervision at home or during hemodialysis to improve physiological outcomes. Patients' lives will improve when nurse-led clinical interventions are incorporated into standard treatment.